Keeping track of promised rewards: Obesity predicts enhanced flexibility when learning from observation. (1st December 2018) - Meemken, Marie T.; Kube, Jana; Wickner, Carolin; Horstmann, Annette
Abstract: Goal-directed behaviour depends on successful association of environmental cues with reward or punishment. Obesity has been linked to diminished learning success in this domain. In contrast, here we demonstrate superior learning in obese participants independent of reward type. We tested association learning in 85 participants with a wide body-mass-index (BMI) range (lean to obese) in four probabilistic reversal-learning experiments. Experiments differed regarding learning mode (active and passive) and reward stimulus (pictures of snack food and money). Food and monetary rewards were adjusted regarding their motivational value in order to allow a direct comparison of related learning characteristics. Our results reveal enhanced associative learning in obese compared to normal-weight participants – reward-independently for expectancy updating and specifically for food-rewards for initial acquisition. When comparing the influence of continuous BMI in active and passive learning, food reward was associated with opposite effects of BMI on performance. Our data indicate generalized, weight-dependent differences in essential reward-learning, though particularly for food reward. We thereby argue that flexible updating of reward-related information may in fact be enhanced in people with obesity – and, thus, possibly promote unhealthy food choices in modern society.